Prevalence and Antibiotic Resistance of Salmonella spp. and Campylobacter spp. Isolated from Retail Chickens in Saudi Arabia - Sulaiman F. Aljasir; Sahar A. Allam (Microbiology Research)
Foodborne pathogens such as Salmonella spp.and Campylobacter spp. pose significant threats to the safety of broiler meat worldwide. However, data on their prevalence in retail chicken meat in Saudi Arabia are scarce. This context mainly concerns the vast poultry market in Saudi Arabia, which may double by 2030. The overall objective of this study was to determine the prevalence and antibiotic resistance of Salmonella spp. and Campylobacter spp. in retail chickens from small, medium-sized, and large production companies in Saudi Arabia. Of the 212 chicken samples tested, Salmonella was detected in 9.3% of samples, all identified as Salmonella enterica serovar Enteritidis. Campylobacter was more prevalent, found in 35.8% of samples, with Campylobacter jejuni accounting for 26.4% and Campylobacter coli for 9.3%. Pathogen prevalence was higher in small-scale than in medium-sized and large producers. Salmonella Enteritidis isolates were resistant to nalidixic acid (90%), amoxicillin-clavulanic acid, and tetracycline (70%). Most Campylobacter coli isolates (90%) exhibited resistance to erythromycin, clindamycin, and gentamicin, followed by tetracycline (80%). Campylobacter jejuni isolates showed high resistance to erythromycin, clindamycin, tetracycline, azithromycin, and nalidixic acid (75–92%). Multidrug resistance (MDR) was observed in all Campylobacter jejuni isolates, 90% of Campylobacter coli isolates, and 70% of Salmonella isolates. These findings underscore the urgent need for adherence to food safety guidelines, particularly in small-scale poultry farms. The pervasive presence of MDR Salmonella spp. and Campylobacter spp. in broiler meat calls for enhanced surveillance, stricter enforcement of food safety practices, and public health initiatives to mitigate the risk of foodborne diseases in Saudi Arabia.